PENERAPAN METODE CRASHINGPROYEK PEMBANGUNAN ELIZABETH BUILDING RS. SANTO BORROMEUS PAKET 1 BANDUNG - Vincensius Palma Ragajiwandana Handri Putra; Arief Andriansyah; Mochammad Agung Wibowo; Bambang Pudjianto (Jurnal Karya Teknik Sipil, 2014)
Project scheduling system is of great importance in the implementation of construction project. To create an effective implementation of construction projects and efficient, all sorts of things should be well planned. In planning the construction of St. Elizabeth Hospital Building borromeous package 1 in Bandung , the author intends to carry out the project duration by accelerating simulation takes into account the magnitude of the project costs incurred. Authors applied the method to simulate the acceleration of crashing the project. In completing this final project, the authors use multiple sources of data, namely the curve S plan, budget plan (RAB), shop drawings projects, and interviews with experts. The research methods used in the final project is to design a network (network planning), calculate the amount of labor required, calculate the costs (direct costs) and indirect costs (indirect costs) on any activity that changes due to changes in the duration of implementation, acceleration duration of the implementation of each heading of work, calculation of cost slope, and the determination of cost and optimum duration of crashing as a result of the application of the method .Final results on Elizabeth Building Development projects RS . Santo Borromeous package 1 Bandung, crashing process is done in two scenarios in which each - each carried 11 times simulation. Based on the graph the relationship between time and cost, obtain the most optimal duration, ie the duration of the minimum total cost is the total project duration of 259 days on the job Crashing 10 occurred in the 1st floor with a slope that is equal to the value of cost Rp.1,861,065.00 per days. Shortening the duration of the Structural Work Level 1 for 7 days, from the normal duration Structural Work Level 1 by 77 days to 70 days . This causes a change in direct costs (direct costs) the normal duration of Rp.46.892.151.077, 89 increased by Rp.117.521.52, be Rp.47.009.672.594.89 , changes in indirect costs (indirect costs) the normal duration of Rp.1,484 .832.000,00 reduced by Rp.428.316.923,00 to Rp. 1,056,515,077.00 and the total cost of the changes from the normal duration of the cost Rp.48.376.983.077,89, reduced by Rp.310.795.400 becomes Rp.48.066.187.677,89. Changes in the cost of the total project cost of the project is equal to ± 0.64 % .